Sistem Pendukung Keputusan Menggunakan Metode Analytical Hierarchy Process (AHP) dalam Penentuan Kualitas Kulit Sapi dalam Produksi Kebutuhan Rumah Tangga - Daeng Saputra Perdana; Sarjon Defit; Sumijan (Jurnal Informasi dan Teknologi, 2021)
Cowhide is the outermost part of beef that can be used in the product process, namely the finished skin in the production of household needs. The purpose of this study is to provide convenience in determining the quality of cowhide in household production needs. The data processed in this study were 6 alternatives. Cowhide quality data obtained at the UPDT Leather Processing Padang Panjang. There are several types of cowhide which have good, medium and poor quality levels. Furthermore, the data is processed manually using the Analytical Hierarchy Process method and continued by using the super software decisions as testing. The processing stage is to determine the weight of each criterion, provide an assessment (pair-wire comparation), summarize all the results of the assessment (overall composite weight). The results of the data processing are continued by calculating the level of accuracy. The result of the test on this method is that 98% of the cowhide has quality with vegetable cowhide based on the quality level of the given criteria. The testing decision making system has been able to identify the specific quality of cowhide. Through the Analytical Hierarchy Process method, the level of accuracy can be quite accurate and can help producers improve accuracy in identifying the quality of cowhide in household production needs.